THE INFLUENCE OF LED LIGHTING TECHNOLOGY AS A STRATEGY FOR BY-CATCH REDUCTION IN FISHING POTS - Haruna; Hehanussa, Kedswin G.; Tawari, Ruslan H.S.; Silooy, Frentje D.; Sangadji, Selfi (Departemen PSP IPB, 2025)
Bycatch refers to the unintentional capture of non-target species, including fish with no commercial value or those that are protected. This issue has raised significant concern in the fisheries industry, as it contributes to overfishing and degradation of marine ecosystems. This study aimed to evaluate the effect of LED lighting on fish pot catch performance. The experiment was conducted from August to September 2023 in the waters of Sole Village, West Seram Regency, Maluku, Indonesia. An experimental fishing method was applied, comparing three treatments: fish pots without light (control), with blue LED light, and with green LED light. Across nine fishing trials, a total of 193 fish were caught, consisting of 53 individuals (27.32%) from pots without light, 108 individuals (55.67%) from blue LED pots, and 33 individuals (17.01%) from green LED pots. The composition of catch indicated that blue LED pots captured 75.00% target species and only 25.00% bycatch, compared to green LED pots (48.48% target : 51.52% bycatch) and pots without light (15.09% target : 84.91% bycatch). Statistical analysis showed no significant difference in total catch among treatments (p>0.05), but the blue LED pots recorded the highest productivity at 19.889 grams/trip/pot. These findings demonstrate that blue LED lighting not only enhances the catch of target species but also effectively reduces bycatch, thereby improving gear selectivity and supporting sustainable fisheries management. Key words: blue led light, by-catch, green led light, pots